Transcranial Magnetic Stimulation Alleviates Levodopa-Induced Dyskinesia in Parkinson's Disease and the Related Mechanisms: A Mini-Review - Wu, Yi; Cao, Xue-bing; Zeng, Wei-qi; Zhai, Heng; Zhang, Xiao-qian; Yang, Xiao-man; Cheng, Chi; Wang, Jia-ling; Yang, Xiao-mei; Xu, Yan (Frontiers in Neurology, 2021)
After long-term use of levodopa, Parkinson's patients almost inevitably develop dyskinesia, a kind of drug side effect manifesting as uncontrollable choreic movements and dystonia, which could be crippling yet have limited therapeutic options. Transcranial magnetic stimulation is the most widely studied non-invasive neuromodulation technology to treat levodopa-induced dyskinesia. Many studies have shown that transcranial magnetic stimulation has beneficial effects on levodopa-induced dyskinesia and is patient-tolerable, barely with reported adverse effects. Changes in brain connectivity, neuroplasticity, neurotransmitter, neurorestoration, and blood flow modulation could play crucial roles in the efficacy of transcranial magnetic stimulation for levodopa-induced dyskinesia. The appearance of new modes and application for emerging targets are possible solutions for transcranial magnetic stimulation to achieve sustained efficacy. Since the sample size in all available studies is small, more randomized double-blind controlled studies are needed to elucidate the specific treatment mechanisms and optimize treatment parameters.